Analisis Penerapan Single Page Application Menggunakan Teknologi AJAX dan REST API (Studi Kasus :Sistem Informasi Reservasi Wisma Tamu UKSW) - Adib Luqman Azhari; Radius - Tanone (Maranatha University Press, 2017)
Developments of web for information system today are really popular. We can access the system from anywhere by internet connection. This paper focus on design of the web application that using Single Page Application concept. Using AJAX technology the application will provide an interactive user experience, also the effective and efficiency usage of bandwith also be considered. The result of this paper shows that implement Single Page Application concept still make the web bandwith usage effective and efficient if accessible by user.Â Keywordsâ€” Single Page Application, AJAX, REST API.